Indolent course of cutaneous gamma‐delta T‐cell lymphoma. (4th February 2013) - Endly, Dawnielle C.; Weenig, Roger H.; Peters, Margot S.; Viswanatha, David S.; Comfere, Nneka I.
<x xml:space="preserve">Abstract</x> Cutaneous gamma‐delta T‐cell lymphoma (γδTCL) is a rare malignancy that typically displays an aggressive clinical course. We present an unusual case of a 57‐year‐old woman with a 3‐year history of lower extremity nodules. Histopathologic, immunophenotypic and molecular genetic studies revealed a clonal, predominantly pannicular gamma‐delta T‐cell infiltrate, leading to a diagnosis of cutaneous γδTCL. The clinical course was characterized by rapid improvement within months of starting systemic corticosteroids, with relapse in ulcerations but no new lesions more than 3 years after onset of disease. Our case and seven previously reported patients with indolent and relatively localized cutaneous γδTCL provide evidence that not all cases of this entity carry a poor prognosis. This indolent subset adds complexity to treatment of cutaneous γδTCL.